2015
DOI: 10.1002/2014ja020923
|View full text |Cite
|
Sign up to set email alerts
|

A model for electric field enhancement in lightning leader tips to levels allowing X‐ray and γ ray emissions

Abstract: A model is proposed capable of accounting for the local electric field increase in front of the lightning stepped leader up to magnitudes allowing front electrons to overcome the runaway energy threshold and thus to initiate relativistic runaway electron avalanches capable of generating X-ray and γ ray bursts observed in negative lightning leader. The model is based on an idea that an ionization wave, propagating in a preionized channel, is being focused, such that its front remains narrow and the front electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(103 citation statements)
references
References 82 publications
4
99
0
Order By: Relevance
“…Our results thus stress the role in maintaining the corona played by poorly understood processes such as the inception of counterpropagating streamers Luque et al, 2016) or the propagation of successive ionization waves along preexisting channels (Babich et al, 2015;Nijdam et al, 2014;Phelps, 1974;Rison et al, 2016). However, at around 100 ns, the overall conductivity of a streamer channel decays, stalling 10.1029/2019GL082063 the increase in temperature.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our results thus stress the role in maintaining the corona played by poorly understood processes such as the inception of counterpropagating streamers Luque et al, 2016) or the propagation of successive ionization waves along preexisting channels (Babich et al, 2015;Nijdam et al, 2014;Phelps, 1974;Rison et al, 2016). However, at around 100 ns, the overall conductivity of a streamer channel decays, stalling 10.1029/2019GL082063 the increase in temperature.…”
Section: Discussionmentioning
confidence: 52%
“…This field triggers either new streamer burtsts, as observed by Kochkin et al (2014) or ionization waves retracing previous streamers, as proposed by Babich et al (2015). Nonetheless, the relatively poor conductivity of a streamer corona together with a variable potential at the leader tip imply that there is often a significant electric field within the corona.…”
Section: Discussionmentioning
confidence: 96%
“…We model the effects of small‐scale air density perturbations and ionization by a preceding streamer as suggested in Babich et al (2015), Eichwald et al (1996), Navarro‐González et al (2001), Hill and Robb (1968), Kacem et al (2013), Liu and Zhang (2014), Marode et al (1979), Villagrán‐Muniz et al (2003), and Plooster (1970). We choose sinusoidal air density perturbation in the radial direction with the minimum on the axis ( r = 0) and the maximum at the outer boundary ( r = L r ) nj(r)=n0()1ξjcos(/Lr);j=0,,4 where n 0 =2.55·10 25  m −3 is the background neutral density at sea level and ξ j = 0−4 is the perturbation amplitude of the j 'th profile simulated.…”
Section: Methodsmentioning
confidence: 99%
“…They were first observed in 1994 from the Compton Gamma‐ray Observatory satellite (Fishman et al, 1994) and later confirmed by other space‐based observations (Briggs et al, 2010; Marisaldi et al, 2010; Smith et al, 2005). X‐rays have also been observed at closer proximity to the source with sensors on the ground and on balloons (Dwyer, 2004; Mallick et al, 2012; Moore et al, 2001) and in high‐voltage laboratory discharge experiments of long sparks (Babich et al, 2015; Dwyer et al, 2005; Kochkin et al, 2014, 2016). The X‐ray and γ ‐ray are produced by high‐energy, runaway electrons through the bremsstrahlung process; however, the acceleration process of these electrons is still under debate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation